Reviewing the principles of corporate governance in islamic financial institutions: the importance of islamic values / Daing Maruak Sadek ... [et al.] - Maruak Sadek, Daing; Abas, Zakaria; Abd Rahim, Khilmy; Anuar, Azyyati; Wan Omar, Wan Nor Faaizah; Yahaya, Ahmad Fauzi (Universiti Teknologi MARA, Kedah, 2020)
The lack of theoretical and empirical research in investigating the principles of Islamic corporate governance in IFIs is the driving force behind this research, as part of the effort to address the issue and thus finding a better solution for corporate governance practices in IFIs within the Islamic financial industry. It is argued the establishment of principles on corporate governance might not be satisfactory whereby there is a compulsion to reevaluate the corporate governance principles of IFIs. Thus, the objective of this paper is to review the principles of corporate governance under the Guidelines on Corporate Governance for Licensed Islamic (GP1-i) in Islamic Financial Institutions. Furthermore, to identify the importance of Islamic values in corporate governance based on Al-Quran and Al-Sunnah. Generally, it is crucial for corporate governance in Islamic banks to have a standardized rules, by the standard setting bodies of Islamic finance to curb the problem of conventional governance weaknesses. IFIs as an Islamic organization that governed by the Islamic principles, must firmly monitor and fulfil their responsibilities as guided by the Islamic law of Sharia’. Thereby, it is required to review the principles of corporate governance which will be supported by the importance of Islamic values. It is hoped this study will contribute to a better understanding of the corporate governance issues of IFIs in Malaysia and to have a deepen analysis of corporate governance with a strong Islamic foundation which refers to Al-Quran and Al-Sunnah.